The concept of law - Hart, H. L. A. (Herbert Lionel Adolphus), 1907-1992. (United Kingdom : Oxford University, 2012)
Fifty years on from its first publication, The Concept of Law is still the starting point for the study of legal philosophy and is widely heralded as a classic work of modern philosophy. This third edition features a new introduction by Leslie Green, looking at Hart's work from the perspective of modern jurisprudence.
Introduction ; 1. Persistent Questions ; 2. Laws, Commands, and Orders ; 3. The Variety of Laws ; 4. Sovereign and Subject ; 5. Law as the Union of Primary and Secondary Rules ; 6. The Foundations of a Legal System ; 7. Formalism and Rule-Scepticism ; 8. Justice and Morality ; 9. Laws and Morals ; 10. International Law ; Postscript
Includes bibliographical references (pages 277-325) and index.
Keywords: Jurisprudence -- Methodology; Law -- Philosophy